Immunobiology roles of the human CD161 receptor in T cells - Tong, Bainan; Wang, Mingxuan; Liu, Lu; Yang, Xinyue (Frontiers in Immunology, 2025)
Human C-type lectin-like molecule CD161 is a type II transmembrane protein expressed on the surface of various lymphocytes within both the innate and adaptive immune systems. CD161 serves as a marker for innate-like T cells and IL-17-producing cells. However, the meaning of these T cells expressing CD161 has not yet been fully determined. Is CD161 merely a phenotypic marker used to identify T cells that are in a common state of activation and/or lineage? Or does this C-type lectin itself have important effector functions? This article aims to explore the latest research progress on CD161-expressing T cells, particularly human αβTCR+T and γδTCR +T cells, and evaluate the importance of CD161 expression on immune function and human diseases through this research.